PEMBERDAYAAN ANAK KELUARGA MISKIN MELALUI COMMUNITY BASED LEARNING RUMAH PINTAR BANGJO SEMARANG - Zahra Nuranggriyan; Rendi Agung Febrianto (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
Poverty creates a continuous cycle of educational poverty that hinders children from low-income families access to quality education. This research examines the implementation of Community Based Learning model at Rumah Pintar Bangjo Community in empowering children from poor families and identifies supporting and inhibiting factors. This research employs a qualitative descriptive case study approach with 6 informants through in-depth interviews, 4 month participatory observation, and documentation study. Data analysis utilized thematic analysis techniques combined with participatory SWOT (Strengths, Weaknesses, Opportunities, Threats) framework. The research findings that Community Based Learning successfully integrates community experiences with academic learning through the principle “from the community, by the community, for the community”. The program improved literacy, self confidence, life skills, and social abilities. The program implemented through Focus Group Discussion, project-based learning, and outing class methods proved effective in enhancing children's learning motivation, with several assisted children successfully continuing their education to senior high school and higher education levels. The findings reinforce the urgency of community based nonformal education as alternative solution to address educational access disparities for marginal groups. Strategies for strengthening volunteer coordination, continuous training, and funding diversification are key to program sustainability